Application of Macro-Ergonomic Analysis and Design to Optimize Make-to-Order Production Systems in the Laundry Machine Industry - Ma'ruf, Farid; Arifin, Muhammad Rowi (Department Industrial Engineering, University of Muhammadiyah Malang, 2026)
Small and medium-sized manufacturing enterprises (SMEs) operating under make-to-order (MTO) systems frequently experience productivity and occupational health issues due to misalignment among organizational, technical, and human factors. This study applies the Macro-Ergonomic Analysis and Design (MEAD) framework to systematically diagnose and improve a manufacturing work system from a sociotechnical perspective. A descriptive, qualitative approach was employed, utilizing interviews, questionnaires, and workplace observations that involved production workers and management. The ten stages of MEAD were implemented to identify critical variances, analyze interactions between subsystems, and develop prioritized improvement alternatives. The results indicate that unfavorable physical environmental conditions—particularly excessive heat and noise—constitute dominant systemic variances that contribute to employee fatigue, work stress, and reduced operational effectiveness. Based on a structured evaluation of alternatives, integrated improvement strategies emphasizing environmental control, risk awareness, and organizational support were proposed. This study demonstrates the usefulness of MEAD as a holistic and adaptive framework for redesigning work systems in SMEs. It contributes empirical evidence to the limited macro-ergonomics literature in MTO manufacturing contexts, particularly in developing countries.